Global citizenship education a critical introduction to key concepts and debates - Sant, Edda; Davies, Ian 1957-; Shultz, Lynette; Pashby, Karen; Shultz, Lynette (Bloomsbury Academic, 2018)
Global Citizenship Education explores key ideas and issues within local, national and global dimensions. Including examples and case studies from across the world, the authors draw on ideas, experiences and histories within and beyond 'the West' to contribute to multifaceted perspectives on global citizenship education. In concise chapters, the authors set out the key concepts and debates within the field. Global citizenship education is contextualized within key educational frameworks, including citizenship education, global education, development education and peace education. Edda Sant, Ian Davies, Karen Pashby and Lynette Shultz explore the different ways in which global citizenship can be taught, learned and assessed in formal and informal contexts. Including examples from a wide range of education institutions, chapters provide overviews of policy making and international practices borne out of different approaches to global citizenship education. With each chapter including a summary of key issues, an annotated list of key resources, an exercise for students and a further reading list, Global Citizenship Education will aid understanding of this complex and debated area of study
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references (pages 215-230) and index
Why Global Citizenship? -- Why Global Citizenship Education? -- Global Rights and Duties -- Imagining Global Communities through a Decolonial Ethic of Global Citizenship -- Global Identities -- National and Global Citizenship -- Planetary and Global Citizenship -- Citizenship Education -- Social Justice -- Development Education -- Character Education -- Global Education -- Peace Education -- Diversity Education -- Education for Sustainable Development -- Research -- Curriculum -- Community Action -- Teaching and Learning Methods in Global Citizenship Education -- Evaluation
Keywords: Bildung; Internationaler Vergleich; International education